VD_FINDINFO HC / 2009 / 478 vom 20. November 2009 - VD Tribunal cantonal (2009)
FAUTE, SURSIS À L'EXÉCUTION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 43 ch. 1 CP, 47 CP, 411 let. i CPP, 415 CPP